Portugal - Asensio, M. (Health politics in Europe: A handbook, 2021)
Health Politics in Europe: A Handbook is a major new reference work, which provides historical background and up-to-date information and analysis on health politics and health systems throughout Europe. In particular, it captures developments that have taken place since the end of the Cold War, a turning point for many European health systems, with most post-communist transition countries privatizing their state-run health systems, and many Western European health systems experimenting with new public management and other market-oriented health reforms. Following three introductory, stage-setting chapters, the handbook offers country cases divided into seven regional sections, each of which begins with a short regional outlook chapter that highlights the region's common characteristics and divergent paths taken by the separate countries, including comparative data on health system financing, healthcare access, and the political salience of health. Each regional section contains at least one detailed main case, followed by shorter treatments of the other countries in the region. Country chapters feature a historical overview focusing on the country's progression through a series of political regimes and the consequences of this history for the health system; an overview of the institutions and functioning of the contemporary health system; and a political narrative tracing the politics of health policy since 1989. This political narrative, the core of each country case, examines key health reforms in order to understand the political motivations and dynamics behind them and their impact on public opinion and political legitimacy. The handbook's systematic structure makes it useful for country-specific, cross-national, and topical research and analysis.